CERAI DENGAN ALASAN SALAH SATU PASANGAN MEMILIH CHILDFREE PERSPEKTIF KOMPILASI HUKUM ISLAM - Syafiq Riza Hasan; Farchan Mu'aziz; Teguh Dwi Cahyadi (Al-Majaalis : Jurnal Dirasat Islamiyah, 2023)
ABSTRACT Islam is a religion that encompasses all aspects of life. One of them is that Islam pays attention to the continuity of human life through marriage. However, in reality, married life is not as smooth as imagined. Many married couples face disharmony in their marriage, which often leads to divorce. Divorce can occur for various reasons. As time progresses, more complex problems arise, one of which is known as "childfree." It is possible that the thoughts of the married couple will change with the changing circumstances and the passage of time. In such a situation, when one partner decides not to have children while the other partner chooses to remain childfree, a lack of harmony arises between them, leading to a new problem that may result in divorce. The aim of this study is to determine whether the reasons for choosing childfree can be used as a basis for divorce, either through "cerai talak" (divorce initiated by the husband) or "cerai gugat" (divorce initiated by either spouse). Considering that these reasons are not explicitly stated in the regulations. The method used in this study is a qualitative research approach. The research findings indicate that reasons for divorce not regulated by the Islamic Law Compilation (KHI) or other marriage regulations can be considered as the legal grounds for divorce. Divorce due to one partner choosing to be childfree can be categorized under point (e) or point (f) of Article 116 of the Islamic Law Compilation. Keywords: childfree, Islam, divorce, KHI.